PENGEMBANGAN KECERDASAN SPIRITUAL PESERTA DIDIK DI SDIT WIHDATUL UMMAH MAKASSAR
The main problem in this study is the development of students’ spiritual intelligence in SDIT Wihdatul Ummah Makassar. This study aims: 1) to know the methods of developing spiritual intelligence of students, 2) to know the implementation of developing spiritual intelligence in extracurricular activities of students, 3) to know the various supporting and inhibiting factors for developing spiritual intelligence of students and the solution, 4) find out the results of developing the spiritual intelligence of students. This research is a qualitative research conducted in the form of a case study. The research location is SDIT Wihdatul Ummah Makassar. Furthermore, the data collection methods used are observation, interview, documentation and reference tracking. Furthermore, data processing and analysis techniques are carried out by means of data reduction, data presentation, and conclusion drawing. The results of this study indicate that: 1) The method of developing spiritual intelligence is applied by teachers in SDIT Wihdatul Ummah Makassar, namely the lecture method, the method of spiritual stories, the method of involving students in religious rituals, the method of giving assignments and the question and answer method. 2) Implementation of the development of spiritual intelligence of students in extracurricular activities at SDIT Wihdatul Makassar, namely tarbiyat al-aula>d, tah